Extracellular vesicles: Targeting the heart - Xin Yin; Xin Yin; Xin Yin; Li-Hong Jiang; Li-Hong Jiang (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases rank the highest incidence and mortality worldwide. As the most common type of cardiovascular disease, myocardial infarction causes high morbidity and mortality. Recent studies have revealed that extracellular vesicles, including exosomes, show great potential as a promising cell-free therapy for the treatment of myocardial infarction. However, low heart-targeting efficiency and short plasma half-life have hampered the clinical translation of extracellular vesicle therapy. Currently, four major types of strategies aiming at enhancing target efficiency have been developed, including modifying EV surface, suppressing non-target absorption, increasing the uptake efficiency of target cells, and utilizing a hydrogel patch. This presented review summarizes the current research aimed at EV heart targeting and discusses the challenges and opportunities in EV therapy, which will be beneficial for the development of effective heart-targeting strategies.